Andromeda galaxy vs Milky Way galaxy - Torosyan, A. A.
Some physical features of the Andromeda galaxy are compared with their counterparts in the Milky Way to demonstrate that the Andromeda galaxy has traversed a longer evolutionary path. One of the evolutionary dependents in galaxies is the metallicity factor. The metallicity radial gradient in galaxies can also be used for this purpose. Most probably, the globular cluster system in galaxies can also serve for this purpose. We propose that dark energy interacts with matter at all levels and plays a role in controlling its evolution, particularly through destructive processes. As a result, we observe phenomena such as metalpoor globular clusters and the blueshift of certain galaxies—effects that, in our view, cannot be fully explained by the Doppler effect alone, but may instead reflect an underlying evolutionary mechanism.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture